Productivity and Stock Returns: 1951 - 2002 - Parhizgari, A.M.; Aburachis, Abe (Universiti Utara Malaysia Press, 2003)
There is considerable concern whether the decline in stock market returns will eventually exert negative changes in the productivity data. This paper examines the long run, or the equilibrium, relationship between productivity and stock returns for the 1951-2002 period. It introduces the notion of equilibrium as represented by the co-movements of economic variables in the long run. This notion is viewed to be broader than the economic theory definition of equilibrium that usually means market clearance. Acknowledging that structural changes in economic time series are hard to detect, an alternative approach employing pair-wise and multifactor cointegration along with VAR modeling is employed. Within this framework, the relationships among productivity, stock prices (returns), investment, and corporate cash flows are pair-wise and jointly investigated. The results indicate that productivity and stock prices share a common trend; so do the stock prices and corporate net cash flows. The long-run common trend between investment and stock prices on the other hand is not so clear. The implications of these results for investors and policy-makers are discussed.